Blender 3D incredible machines : a comprehensive guide to hard-surface models, including polygon modeling, texture painting, and rendering /: a comprehensive guide to hard-surface models, including polygon modeling, texture painting, and rendering. (2022) - Belec, Arijan
No abstract available